Eficácia da terapia de fotobiomodulação no tratamento do trismo relacionado à radioterapia de cabeça e pescoço: um ensaio clínico de braço único - Borges, Marcela Maria Fontes (2023)
Introduction: Trismus is a common adverse effect in patients with head and neck cancer, where patients have a limitation of mouth opening (<35 mm), which can lead to an impairment of maxillomandibular function, with surgery and radiotherapy being the most involved. Objective: To evaluate PBMT photobiomodulation therapy for the treatment of trismus in patients undergoing radiotherapy for head and neck cancer (HNC). Material and methods: Sixteen patients who had a mouth opening <35mm and were undergoing RT were included. Patients were evaluated daily before and after PBMT application, measuring mouth opening and performing pain scores for the masticatory muscles using the VAS scale. The infrared laser (~808 nm) was used extraorally, power of 0.1W, energy of 3J, 30s (107 J/cm2) per point, applied to the anterior temporal, masseter and temporomandibular joints (TMJ) muscles. An intraoral stitch was performed on the medial pterygoid muscle. Results: The patients' average mouth opening increased by more than 7 mm over the course of treatment. Pain scores in the initial days showed immediate reduction after PBMT on the ipsilateral side in the muscles and TMJ. During the PBMT applications, there was a significant reduction in pain scores in all muscles and in the TMJ. The radiation dose of all patients was above 40Gy, which is the threshold dose for the risk of developing trismus. Conclusions: PBMT controls muscle pain and reduces the limitation of mouth opening in CCP during radiotherapy. More studies are needed to assess the preventive capacity of PBMT protocols related to CCP RT trismus.